2019
DOI: 10.18632/oncotarget.26533
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced sphingolipid signaling is maintained as a core proponent of a cancerous phenotype in spite of metabolic pressure and epigenetic drift

Abstract: Tumor heterogeneity may arise through genetic drift and environmentally driven clonal selection for metabolic fitness. This would promote subpopulations derived from single cancer cells that exhibit distinct phenotypes while conserving vital pro-survival pathways. We aimed to identify significant drivers of cell fitness in pancreatic adenocarcinoma (PDAC) creating subclones in different nutrient formulations to encourage differential metabolic reprogramming. The genetic and phenotypic expression profiles of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…22,23 Additionally, Speirs et al identified SPHK1 as a key driver of the conserved S1P: Ceramide imbalance in pancreatic cancer subcultures and therefore one of the central controlling hubs of rheostat machinery. 22 The most recent literature data suggested that sphingolipid signaling pathway could be an important novel therapeutic target to suppress proliferation across pancreatic tumors made up of heterogeneous cell populations, with recognition of potential of SPHK1 inhibitors as an approach to reverse healthy balance of pro-and anti-apoptotic signaling in pancreatic cancers. 22,[24][25][26] Additionally, predictions identified synergism between pan-HDAC inhibitor and SPHK1 inhibitor to be highly scored (in first 5% of the ordered list of predictions) (Table 1 and Supplementary Data File 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…22,23 Additionally, Speirs et al identified SPHK1 as a key driver of the conserved S1P: Ceramide imbalance in pancreatic cancer subcultures and therefore one of the central controlling hubs of rheostat machinery. 22 The most recent literature data suggested that sphingolipid signaling pathway could be an important novel therapeutic target to suppress proliferation across pancreatic tumors made up of heterogeneous cell populations, with recognition of potential of SPHK1 inhibitors as an approach to reverse healthy balance of pro-and anti-apoptotic signaling in pancreatic cancers. 22,[24][25][26] Additionally, predictions identified synergism between pan-HDAC inhibitor and SPHK1 inhibitor to be highly scored (in first 5% of the ordered list of predictions) (Table 1 and Supplementary Data File 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipid rheostat, and particularly equilibrium between ceramide and S1P, have been just recently characterized as one of the critical regulator of pro-and anti-apoptotic singling in metabolically dynamic pancreatic cancers. 22,23 Additionally, Speirs et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1P is a bioactive type of sphingolipid, which is converted from ceramide and intracellular S1P was catalyzed mainly by the key sphingosine kinase isoforms, SPHK1 29 . Previous studies have demonstrated that high expression of SPHK1 in tumors was associated with poor prognosis of pulmonary, gastric, pancreatic and colonic cancer patients 3033 and high expression of phosphorylated SPHK1 could promote cell growth and metastasis 34 . In our work, we consistent expression of SPHK1 with POTEE from both endogenous and exogenous evidence, and they are also positively correlated in the tumor samples of CRC patients.…”
Section: Discussionmentioning
confidence: 99%